Summer Water Vapor Transport and Sources in Anomalous Precipitation Years over the Qinba Mountains - Yiru YANG; Bin WANG; Shuangshuang LI; Li XING; Xingli MAO; Wei SHANG; Peihong SHI; Ying CHENG; Keqin DUAN (Gaoyuan qixiang)
The Qinling-Daba Mountains （Qinba Mountains） are referred to as the‘Central Water Tower’of China.They constitute the main transitional zone between the north and south and play a crucial regulatory role in the evolution of the natural environment.However， the current understanding of the contributions and causes of water vapor sources in the Qinba Mountains remains unclear， significantly impeding the comprehension of the underlying mechanisms that influence the geographical division between the north and south of China.In this study， we simulate the vapor trajectory in summer of years with high and low precipitation from 1970 to 2020 using the HYSPLIT model， and calculates the anomalies of vapor and wind using Eulerian method.The characteristics of vapor transport pathways and source contributions at different vertical levels from June to August over the Qinba Mountains were systematically analyzed.The results showed that： （1）The main summer water vapor channels in the Qinba Mountains are： the local channel， the Eurasian channel， the Western Pacific channel， the South China Sea channel and the Indian Ocean channel.（2）In terms of channel strength， the main vapor channels at the lower levels in high precipitation years are the local and South China Sea channels； that at the middle and upper levels are the Eurasian channel and the Indian Ocean channel.In the low precipitation year， the main channel at all levels is the Eurasian channel.（3）In terms of source contributions， the main source at the lower level in high precipitation years is the local and the South China Sea， that at the lower level in low years is the local， South China Sea and western Pacific.The main source at the middle and upper levels is the north Indian Ocean.（4）The anomalous characteristics of anticyclones and cyclonic circulation in the southeast have a significant impact on the difference in water vapor transport between high and low precipitation years.This study provides preliminary insights into the vapor transport characteristics during summer over the Qinba Mountains， thereby advancing our understanding of the underlying mechanisms of the Central Water Tower phenomenon and the geographic differentiation role of the Qinba Mountain region.